1998
DOI: 10.1016/s1010-7940(98)00065-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of late reoperations in patients with acute type A aortic dissection: impact of a more radical surgical approach

Abstract: Management of patients with acute type A aortic dissection may include one or more surgical procedures after the initial emergency repair. Reoperations carry a low operative risk with good long-term survival and their incidence is reduced by routine open distal anastomosis and aggressive replacement of the aortic arch. Intimal tear resection and primary anastomosis of the aorta appear to be associated with increased risk of reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 17 publications
3
37
1
Order By: Relevance
“…Although there have been many reports on favorable results of total arch replacement with or without elephant trunk procedure [14,18,[54][55][56], it is still controversial [57][58][59]. Rampoldi et al demonstrated in their large multi-center analysis involving 682 patients with acute type A aortic dissection that the partial arch replacement was associated with reduced mortality [57].…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been many reports on favorable results of total arch replacement with or without elephant trunk procedure [14,18,[54][55][56], it is still controversial [57][58][59]. Rampoldi et al demonstrated in their large multi-center analysis involving 682 patients with acute type A aortic dissection that the partial arch replacement was associated with reduced mortality [57].…”
Section: Resultsmentioning
confidence: 99%
“…A closed technique results in nearuniform PFL persistence in DeBakey I dissections (257,272). Because it facilitated more complete repair and hypothetically reduced PFL risk, ODA became both popular (277) and the accepted surgical norm (14,278). An ODA allows a more accurate approximation of the dissected layers and a direct visual inspection for further arch tears (279).…”
Section: Surgical Management Of the Distal Aortamentioning
confidence: 99%
“…Zero percent to 14% hospital mortality and 8% to 21% long-term mortality have been reported in other series [22][23][24][25], but these series had very small patient cohorts (n ¼ 24, 21, 19, and 17) and even smaller numbers of patients who underwent procedures involving replacement of the entire arch. Of interest, in our series, full arch replacement versus hemiarch replacement was not significantly associated with either operative or long-term mortality (p ¼ 0.54 and 0.28, respectively).…”
Section: Commentmentioning
confidence: 84%